The surface coverage of PEM fuel cell electrodes. (5th January 2016) - Dundar, F.; Pilenga, A.; Tsotridis, G.
Abstract: A quantitative study was conducted on Hydrogen (H2 ), water (H2 O) and carbon monoxide (CO) molecule concentration on a Pt–Ru catalyst surface used for PEM fuel cells. Strongly bonded hydrogen molecules which can withstand 100 ppm CO exposure at 50 °C were calculated as 54% of the total hydrogen bonds present on catalyst surface during pure H2 purge. The very weakly bonded hydrogen molecules that could be removed with pure inert gasses were not taken into account. Additionally, the water and hydrogen molecule content on the surface of the catalyst layer was compared and bonded hydrogen molecule ratios of 33–63% were obtained for different temperatures (25 °C, 50 °C and 75 °C) and relative humidity values (Dew Point Temperatures of 25 °C, 35 °C and 45 °C). Furthermore, 10 ppm CO exposure time at dry conditions was varied from 30 s to 1 h at 50 °C. The majority of the weakly adsorbed hydrogen molecules desorbed in the first 10 min with 300 sccm gas flow over Pt–Ru catalyst layer. The desorption process stopped after 10 min. The hydrogen molecules were bonded strong enough to stick to the surface under 10 ppm CO exposure at 50 °C. The bonded hydrogen molecule ratio of 66–67% was calculated for 10–60 min of 10 ppm CO exposure. Highlights: Strong and weak Hydrogen bond ratios on Platinum–Ruthenium surface were determined as 54% and 46% respectively. Water molecule coverage during humidified Hydrogen gas purge at different humidity levels and temperatures were determined. Strong bonded Hydrogen molecules removal rate was determined under different CO exposure times. The hydrogen content on the surface dropped approximately by 35% after 10 min of CO exposure. Desorption of weakly bonded Hydrogen molecules were monitored.